2021
DOI: 10.1007/s00018-021-03864-0
|View full text |Cite
|
Sign up to set email alerts
|

Localization matters: nuclear-trapped Survivin sensitizes glioblastoma cells to temozolomide by elevating cellular senescence and impairing homologous recombination

Abstract: To clarify whether differential compartmentalization of Survivin impacts temozolomide (TMZ)-triggered end points, we established a well-defined glioblastoma cell model in vitro (LN229 and A172) and in vivo, distinguishing between its nuclear and cytoplasmic localization. Expression of nuclear export sequence (NES)-mutated Survivin (SurvNESmut-GFP) led to impaired colony formation upon TMZ. This was not due to enhanced cell death but rather due to increased senescence. Nuclear-trapped Survivin reduced homologou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 49 publications
2
6
0
Order By: Relevance
“…Of note, also for A172, the amount of senescent cells increased up to 75% at later post-exposure times. In all cell lines, senescence was accompanied by arrest in the G2-phase of the cell cycle, which confirms previous reports [ 8 , 48 ]. All cell lines showed the emergence of polyploid cells (20–30% of the population) upon treatment with 50 µM TMZ and a post-exposure time of 120 h. Very recently, we reported that glioma cells showing a strong accumulation of nuclear Survivin also exhibit an increased polyploid cell population after exposure to TMZ [ 48 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Of note, also for A172, the amount of senescent cells increased up to 75% at later post-exposure times. In all cell lines, senescence was accompanied by arrest in the G2-phase of the cell cycle, which confirms previous reports [ 8 , 48 ]. All cell lines showed the emergence of polyploid cells (20–30% of the population) upon treatment with 50 µM TMZ and a post-exposure time of 120 h. Very recently, we reported that glioma cells showing a strong accumulation of nuclear Survivin also exhibit an increased polyploid cell population after exposure to TMZ [ 48 ].…”
Section: Discussionsupporting
confidence: 91%
“…Overall, our data presented here and previously published indicate that in glioblastoma cells, TMZ induces senescence to a significantly higher level than cell death through apoptosis and necrosis [ 7 , 8 , 43 , 48 ]. Senescence is associated with activation of several anti-apoptotic factors, such as Bcl-2, c-IAP1, and c-IAP2.…”
Section: Discussionsupporting
confidence: 77%
“…Song et al ( 115 ) previously indicated that the knockdown of survivin promoted glioma cell sensitivity to TMZ treatment by inducing the apoptosis of senescent cells. Furthermore, survivin nuclear trapping has been found to facilitate GBM response to TMZ ( 116 ).…”
Section: Oncogenic Lncrnas Promote Tmz Resistance In Gliomasmentioning
confidence: 99%
“…The first well-studied type of RNA as a biomarker is messenger RNA (mRNA), which is a single-stranded RNA transcribed from a specific DNA to guide protein synthesis. A number of mRNAs have been employed in disease diagnosis , or therapy. , For instance, survivin mRNA is known to be upregulated in most cancers, and its expression level is important for early diagnosis and medical prognosis. , To be noted, mRNAs exhibit complex dynamics in cells, including the expression, degradation, and translocation; thus, in situ live-cell imaging of target mRNAs is highly desirable to obtain their spatial–temporal information for better understanding the functions, identifying diseases, and evaluating therapy efficacy …”
Section: Introductionmentioning
confidence: 99%
“…3,4 For instance, survivin mRNA is known to be upregulated in most cancers, and its expression level is important for early diagnosis and medical prognosis. 5,6 To be noted, mRNAs exhibit complex dynamics in cells, including the expression, 5 degradation, 7 and translocation; 8 thus, in situ live-cell imaging of target mRNAs is highly desirable to obtain their spatial−temporal information for better understanding the functions, identifying diseases, and evaluating therapy efficacy. 9 Most available non-polymerase chain reaction (PCR) detection methods rely on probes without signal amplification [e.g., using classic molecular beacons (MBs) 10 or linear templated reactions 11−13 ], where the signal and the target mRNA are in an equivalent ratio (1:1), hindering the detection of low-expression mRNA.…”
Section: Introductionmentioning
confidence: 99%